Knowledge, attitude, and practice study of Middle East respiratory syndrome coronavirus in Oman - Al Araimi, Jabir; Johnson, Anbu Clemensis; Al Araimi, Mohammed Juma (International Journal Of Community Medicine And Public Health, 2023)
Background: In the 21st century, there has been an increase in the spread of various diseases. Middle East respiratory syndrome coronavirus (MERS-CoV) disease is one of them. In order to contain and eradicate the spread of MERS-CoV, assessing public knowledge, attitude, and practice is important. This public study was conducted in the eleven governorates of Oman for its assessment. Methods: A national level cross-sectional survey was conducted online for a period of nine days using a questionnaire that contained forty-one questions. The questions were designed to evaluate public perception and understanding of MERS-CoV disease. The acquired data were analysed using SPSS software. Results: A total of 505 people participated in the survey. The majority of the participants were males from the Muscat region (46%). The ages of the participants were between <20 to 60 years. The survey revealed that 60% of the participants were unaware about the disease (p<0.001) and about 48% (p=0.003) of them were unsure about the symptoms of the disease. Most people had a positive attitude towards preventing the spread of the infection. Adherence to precautionary measures was higher among the female participants (69%, p=0.021). Primary information source for the public was through social media. Conclusions: Overall, the surveyed population had a varied perspective about the disease and fair knowledge on the preventive measures. However, a large percentage of the participants were unclear about the epidemic situation and lacked knowledge on the disease, but showed a positive attitude towards curbing the spread of infection.